The Effect of Corporate Social Responsibility on the Firm Value Moderated by Corporate Governance on Mining Sector Listed on IDX Period 2013-2018 - Destria Kurnianti; Andhi Wijayanto; Andyka Yudha Satria Putra; Novan Yonatan Seilatu (Communications of International Proceedings, 2020)
The aim of this study is to determine the effect of Corporate Social Responsibility on the Firm Value moderated by Corporate Governance on Mining Sector Listed on IDX Period2013-2018. Independent variable of this study is Corporate Social Responsibility as measured by CSRI. Dependent variable of this study is Firm Value with PBV as a proxy. While moderating variable used is Corporate Governance with Audit Committee as the proxy. Then control variable in this study are Firm Size, Profitability, Leverage, and Firm Age. The data used in this study is annual report of Mining Sector listed in Indonesia Stock Exchange (IDX) period 2013-2018. The sampling method of this study is purposive sampling technique. The research model of this study employs panel data analysis with Random Effect Model approach. The empirical result shows that Corporate Social Responsibility does positive effect and significant on Firm Value. Corporate Governance moderated by Audit Committee weakening the relation between Corporate Social Responsibility on Firm Value.
Keywords: Firm Value; Corporate Social Responsibility; Profitability; Leverage; Firm Age.